Integrating the PIECES Framework with Human Computer Interaction to Evaluate User Acceptance of E-Marketplace Information Systems - Fiati, Rina; Zahro, Nafi Inayati; Latifah, Noor (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study evaluates user acceptance of E-Marketplace information systems by integrating the PIECES Framework with a Human–Computer Interaction (HCI) approach. This integration offers a comprehensive view of both technical system performance and user-centered interaction, particularly for users with disabilities. The PIECES Framework assesses system quality and operational effectiveness, while the HCI approach emphasizes usability, user experience, and interaction patterns that influence acceptance and satisfaction. Using an action research design, data were collected via questionnaires from a sample of 30 respondents. The findings indicate that user interest has a partial yet significant effect on behavior, while other variables jointly influence user engagement. Notably, there was a marked increase in user understanding of internet tools—from 27% initially not understanding application use to 91% demonstrating improved comprehension. This progress underscores the importance of accessible and user-friendly design in enhancing trust and perceived security. The results highlight the critical role of consistent interface design, clear navigation, and inclusive visual elements in promoting usability and satisfaction. The study offers valuable insights for system developers and researchers to improve E-Marketplace platforms by aligning technical performance with inclusive, user-centric design—ensuring accessibility for all users, including persons with disabilities, and driving greater digital inclusion in the evolving digital economy.